Revival of Pharaonic Architecture in Synagogues and Masonic Temples: Identity or Inspiration? - Sara Abdoh (Disegnare con, 2020)
The ancient Egyptian architectural elements and motifs had a deep religious philosophy, which is connected to their beliefs in resurrection. This religious philosophy made it difficult to revive those pharaonic architectural symbols, which symbolize ancient Egyptian gods, on the Jewish, Christian, or Islamic places of worship, which have different beliefs than ancient Egyptian religion. For example, we will never find a symbol of an ancient Egyptian god, such as the winged sun disk, which symbolizes the ancient god Horus Behdety, on a synagogue, church, or mosque inside or outside Egypt. But it is surprising that there are ancient Egyptian religious symbols in some Masonic temples, and that prompted me to search for the real motivation that necessitated the presence of such elements on these buildings outside Egypt. The research will discuss the symbolism of ancient Egyptian architectural elements and the reasons for its revival on the synagogues and Masonic temples. DOI: https://doi.org/10.20365/disegnarecon.25.2020.16